2016
DOI: 10.3897/rio.2.e10528
|View full text |Cite
|
Sign up to set email alerts
|

The London Workshop on the Biogeography and Connectivity of the Clarion-Clipperton Zone

Abstract: publisher: Pensoft Publishers articletitle: The London Workshop on the Biogeography and Connectivity of the Clarion-Clipperton Zone journaltitle: Research Ideas and Outcomes copyright: http://creativecommons.org/licenses/by/4.0/ received: 2016-09-16 published: 2016-09-1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The mining pre-prototype vehicle (4.7 × 12 m) presented by GSR is a pickup system based on four nodule collector heads (1 m wide each) using a jet water pump and suction to collect nodules down to 15 cm depth (Global Sea Mineral Resources NV, 2018). A mining operation is anticipated to directly affect over 100 km 2 yr −1 of the seabed and create sediment plumes that can indirectly increase the footprint of mining by a factor of 2 to 5 (Oebius et al, 2001;Glover and Smith, 2003). Nodule mining will clearly have detrimental effects on the benthic ecosystem, but the severity of the impacts is difficult to predict.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mining pre-prototype vehicle (4.7 × 12 m) presented by GSR is a pickup system based on four nodule collector heads (1 m wide each) using a jet water pump and suction to collect nodules down to 15 cm depth (Global Sea Mineral Resources NV, 2018). A mining operation is anticipated to directly affect over 100 km 2 yr −1 of the seabed and create sediment plumes that can indirectly increase the footprint of mining by a factor of 2 to 5 (Oebius et al, 2001;Glover and Smith, 2003). Nodule mining will clearly have detrimental effects on the benthic ecosystem, but the severity of the impacts is difficult to predict.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term surveys of small-scale disturbances or mining tests have shown that the direct impacts of seafloor disturbances may last for over 30 years in the CCFZ Jones et al, 2017). However, such small experiments hardly mimic the cumulative impacts of any single nodule mining operation that could last for 20 years (Glover and Smith, 2003;Jones et al, 2017). Beyond the unpredictable effects of the full-scale mining, the extent of biodiversity and species' ranges in the CCFZ are two major unknowns that prevent the assessment of potential biodiversity loss due to nodule mining.…”
Section: Introductionmentioning
confidence: 99%
“…The APEIs were designated to preserve source populations of species for future recolonization of disturbed areas (Lodge et al, 2014). However, the majority of these APEIs remain unstudied; it is not clear if their environmental conditions and faunas are similar to those of the mining claims (Glover et al, 2016a). As a result, improved knowledge of the drivers structuring biological communities in the CCZ is urgently needed to test the presumed functionality and current spatial arrangement of the APEIs system, and to re-assess the regional environmental plan (ISA, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly problematic as such information is critical to characterise the biodiversity, biogeographic ranges, and connectivity patterns across the entire CCZ in order to make better predictions about the potential impacts of deep-sea mining. In addition, the APEIs designated to preserve regional biodiversity are severely understudied ( Glover et al 2016a ; International Seabed Authority 2020; Jones et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%